A cobalt-free high entropy alloy and its preparation method and application
By designing the composition and preparation process of cobalt-free high-entropy alloys, the nanosheet structure is formed, which solves the problem of insufficient phase strength of the FCC structure, and achieves high strength and plasticity, which is suitable for high mechanical properties structural materials in the nuclear industry.
Patent Information
- Application Number
- CN202311468895.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-11-07
AI Technical Summary
In the prior art, the high entropy alloys with FCC structures are insufficient in strength, making it difficult to meet the demand for high-strength and tough structural materials in the nuclear industry.
A cobalt-free high-entropy alloy is designed, with components including Fe, Ni, Cr, Al and Ti. The microstructure structure of the nanosheet layer is formed through vacuum arc smelting, homogenization treatment, cold rolling treatment and annealing treatment.
The high strength and plasticity of the alloy are achieved, the problem of insufficient FCC structural phase strength is solved, and a high mechanical properties structural material suitable for the nuclear industry is provided.
Smart Images

Figure CN117568690B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high entropy alloy materials, and more specifically relates to a cobalt-free high entropy alloy and a preparation method and application thereof. Background Art
[0002] With social progress and economic development, human demand for energy is increasing. However, the exploitation and use of non-renewable resources such as coal, oil, and natural gas will eventually lead to the depletion of fossil energy resources, and the excessive use of fossil energy will emit a large amount of greenhouse gas CO2. The resulting greenhouse effect will cause global warming, which will seriously damage the earth's ecosystem.
[0003] Nuclear energy is a stable and efficient clean energy. Compared with other power sources such as hydropower, solar energy, and wind energy, nuclear energy has the advantages of stable supply, no gaps, and less constraints from natural conditions. It is expected to become a new energy source to replace traditional fossil energy. In nuclear power plants, reactor structural materials are the foundation of nuclear energy construction and play a key role in the safety, reliability, and operating life of nuclear reactor systems. The service environment of reactor structural materials is complex, so the comprehensive performance of service materials is demanding.
[0004] High entropy alloys have become a potential reactor structural material due to their high strength, high hardness, excellent corrosion resistance, high temperature softening resistance and unique radiation resistance. Studies have shown that the unique structure of high entropy alloys has a certain inhibitory effect on radiation defects. Co resources are a strategic resource with high prices and relatively small reserves in my country. Co produced by high neutron transmutation 60 The increased radioactivity will increase the radiation shielding requirements during neutron irradiation post-processing, which may cause workers to be exposed to higher doses of radiation during nuclear power plant operation and maintenance, increasing the construction cost of the nuclear power plant and creating safety hazards during operation.
[0005] High entropy alloys with FCC structure (face-centered cubic lattice) have advantages such as good plasticity and good machinability, but lack strength. The strength of stainless steel, which is currently widely used, and FeCrAl alloys, which have been popular in recent years, is also below the giga-level.
[0006] In response to existing technical problems, it is now urgently needed to design a cobalt-free alloy that has high strength and toughness, simple processing, and is suitable for structural materials in the nuclear industry. Summary of the invention
[0007] The purpose of the present invention is to provide a cobalt-free high entropy alloy and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] One of the technical solutions of the present invention is to provide a cobalt-free high entropy alloy, wherein the alloy raw materials include, by weight:
[0010] 38-42 parts of Fe, 40-44 parts of Ni, 8-12 parts of Cr, 1-4 parts of Al and 3-6 parts of Ti.
[0011] Furthermore, the cobalt-free high entropy alloy comprises, by weight, 38 to 42 parts of Fe, 40 to 44 parts of Ni, 8 to 12 parts of Cr, 1 to 4 parts of Al and 3 to 6 parts of Ti.
[0012] Furthermore, the molar ratio of Fe, Ni, Cr, Al and Ti in the alloy raw material is 8:8:2:1:1.
[0013] The composition ratio of the cobalt-free high entropy alloy of the present invention enables the alloy to have good workability after homogenization annealing, avoiding cracking failure of the alloy during cold working; within the composition mass ratio range specified in the present application, the alloy can form a nanosheet microstructure in the subsequent thermomechanical treatment.
[0014] The second technical solution of the present invention is to provide a method for preparing the above-mentioned cobalt-free high entropy alloy, comprising the following steps:
[0015] The alloy raw materials are subjected to vacuum arc melting under the protection of an argon atmosphere to obtain an alloy product;
[0016] The alloy product is subjected to homogenization treatment, cold rolling treatment and annealing treatment to obtain the cobalt-free high entropy alloy.
[0017] Furthermore, the vacuum arc melting step includes: the initial arc current is 60-80A, gradually increasing to 145-155A to melt the alloy raw materials, and then increasing the current to 200A and maintaining it for 8-12s to complete the melting.
[0018] Furthermore, the vacuum arc melting is performed at least once, and the vacuum degree is not higher than 0.005Pa.
[0019] Vacuum arc melting ensures the purity and uniformity of the alloy, avoiding alloy oxidation and oxygen infiltration; reasonable current parameters control the stability of the alloy during melting, avoiding raw material burning to ensure the accuracy of the alloy composition.
[0020] Furthermore, the temperature of the homogenization treatment is 1150-1250° C., and the time is 2-4 hours.
[0021] Furthermore, the cold rolling reduction is 75-85%.
[0022] Furthermore, the annealing treatment is performed at a temperature of 600 to 750° C. and for a time of 1 to 8 hours.
[0023] Homogenization annealing reduces the composition segregation caused by solidification and forms a second phase structure of nanoparticles. Larger deformation can harden the alloy, increase deformation energy storage, and lay the necessary foundation for the subsequent formation of nanosheet structure. Annealing in the range of 600-750℃ can produce nanosheets with sufficient density and appropriate size, so that the alloy has strong plasticity and excellent mechanical properties.
[0024] Furthermore, the specific steps of the preparation method include:
[0025] S1, placing the alloy raw materials into a vacuum arc melting furnace for melting under the protection of argon atmosphere, and obtaining the alloy product by copper mold suction casting after melting;
[0026] S2, homogenizing the alloy product at 1150-1250° C. for 2-4 hours and then cooling it to room temperature with water;
[0027] S3, performing at least one cold rolling treatment on the homogenized alloy product;
[0028] S4. The cold-rolled alloy product is subjected to aging annealing at 600-750° C. for 1-8 hours and then water-cooled to room temperature to obtain the cobalt-free high entropy alloy.
[0029] The third technical solution of the present invention is to provide an application of the above-mentioned cobalt-free high entropy alloy as a high-strength structural material in the nuclear industry.
[0030] The present invention discloses the following technical effects:
[0031] The present invention is a high entropy alloy without Co element, which avoids the strong radioactivity of Co after irradiation and reduces the extra cost expenditure of the nuclear industry caused by shielding Co-containing materials. The nanosheet structure formed by the alloy after thermomechanical treatment has high strength and certain plasticity. The present invention provides a composition formula and preparation process of structural materials suitable for the nuclear industry.
[0032] The crystal structure of the cobalt-free high-entropy alloy prepared by the present invention is a single FCC structural phase. The precipitated phase in the alloy is mainly in the form of two-dimensional nanosheets or nanorods, which are densely distributed and have an average grain size of about 2 microns. At the same time, it has excellent tensile mechanical properties, solving the technical problem of insufficient strength of the FCC structural phase in the prior art.
[0033] The cobalt-free high-entropy alloy prepared by the present invention has excellent room temperature and medium-temperature mechanical properties in nuclear industry applications. By utilizing relatively common transition elements and a simple process flow, an alloy material with high mechanical properties that meets the service requirements of nuclear power plant structural materials is prepared, providing an optional material for the high service requirements posed by the extreme working conditions faced in the development of fourth-generation nuclear fusion reactors. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0035] Figure 1 This is a diagram of the preparation process of the cobalt-free high-entropy alloy Fe8Ni8Cr2AlTi sample in Example 1 of the present invention.
[0036] Figure 2 This is a picture of the material prepared in Comparative Example 1 after rolling treatment.
[0037] Figure 3 The tensile curves of the cobalt-free high entropy alloy prepared in Example 1 of the present invention at room temperature (a) and 600°C (b), and the comparison with the room temperature tensile test results of the FeCrAl alloy (c).
[0038] Figure 4 This is the X-ray diffraction pattern of the cobalt-free high entropy alloy prepared in Example 1.
[0039] Figure 5 (a) SEM image and (b) grain size statistics graph of the cobalt-free high entropy alloy prepared in Example 1 of the present invention.
[0040] Figure 6 This is a nanoscale SEM image of the cobalt-free high entropy alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] Preparation of cobalt-free high entropy alloy Fe8Ni8Cr2AlTi:
[0044] S1. Preparation of alloy raw materials: Select single raw materials (Fe, Ni, Cr, Al and Ti) with a purity of 99.9%, clean the surface oxide scale and oil stains, then ultrasonically clean them with acetone, use a hair dryer to dry them, and then prepare each component according to the molar ratio of Fe, Ni, Cr, Al and Ti of 8:8:2:1:1 (the mass percentages are 40.79% Fe, 42.87% Ni, 9.50% Cr, 2.46% Al and 4.37% Ti respectively);
[0045] S2. Place the above alloy raw materials in a water-cooled non-consumable vacuum arc melting furnace in the order of melting point from low to high and size from small to large, evacuate to below 0.005Pa, fill the furnace cavity with argon gas to flush, repeat three times, and then open the arc under the protection of argon gas. The initial arc current is 60-80A, and then gradually increased to 150A to melt the titanium ingot; then move to the raw materials to be smelted, gradually melt the raw materials along the water-cooled copper crucible, and then increase the current to 200A, stay for about 10s, so that the alloy is melted into button ingots; repeat the smelting process 4 times to make the alloy components fully melted and evenly diffused;
[0046] S3, using the copper mold suction casting method, the fully smelted alloy is kept at an arc of 180A for 10 to 20 seconds and then the melt is cast into a plate-shaped water-cooled copper mold (10 mm wide, 5 mm thick, and 60 mm high) to obtain a corresponding plate-shaped alloy product with a thickness of 5 mm;
[0047] S4, placing the alloy product in a heat treatment furnace at 1200° C. for homogenization for 2 h, and then water-cooling to room temperature;
[0048] S5, performing multiple cold rolling processes on the homogenized alloy product until the rolling reduction is 77%;
[0049] S6, subjecting the alloy product after cold rolling to aging annealing at 650° C. for 2 h and then cooling it to room temperature with water to obtain the cobalt-free high entropy alloy;
[0050] S7. Wire-cut the cobalt-free high entropy alloy to obtain a cobalt-free high entropy alloy Fe8Ni8Cr2AlTi sample.
[0051] Example 2
[0052] Preparation of Cobalt-free High Entropy Alloy:
[0053] S1. Preparation of alloy raw materials: select Fe, Ni, Cr, Al and Ti with a purity of 99.9%, clean the surface oxide scale and oil, then use acetone ultrasonic cleaning, use a hair dryer to dry, and then prepare each component according to the molar ratio of Fe, Ni, Cr, Al and Ti of 8:8:2:1:1;
[0054] S2. Place the above alloy raw materials in a water-cooled non-consumable vacuum arc melting furnace in the order of melting point from low to high and size from small to large, evacuate to below 0.005Pa, fill the furnace cavity with argon gas to flush, repeat three times, and then open the arc under the protection of argon gas. The initial arc current is 60-80A, and then gradually increased to 150A to melt the titanium ingot; then move to the raw materials to be smelted, gradually melt the raw materials along the water-cooled copper crucible, and then increase the current to 200A, stay for about 10s, so that the alloy is melted into button ingots; repeat the smelting process 4 times to make the alloy components fully melted and evenly diffused;
[0055] S3, using the copper mold suction casting method, the fully smelted alloy is kept at an arc of 180A for 10 to 20 seconds and then the melt is cast into a plate-shaped water-cooled copper mold (10 mm wide, 5 mm thick, and 60 mm high) to obtain a corresponding plate-shaped alloy product with a thickness of 5 mm;
[0056] S4, placing the alloy product in a heat treatment furnace at 1200° C. for homogenization for 2 h, and then water-cooling to room temperature;
[0057] S5, subjecting the homogenized alloy product to multiple cold rolling processes until the rolling reduction is 85%;
[0058] S6. The alloy product after cold rolling is subjected to aging annealing at 750° C. for 4 hours and then water-cooled to room temperature to obtain the cobalt-free high entropy alloy.
[0059] Example 3
[0060] Preparation of Cobalt-free High Entropy Alloy:
[0061] S1. Preparation of alloy raw materials: select Fe, Ni, Cr, Al and Ti with a purity of 99.9%, clean the surface oxide scale and oil, then use acetone ultrasonic cleaning, use a hair dryer to dry, and then prepare each component according to the molar ratio of Fe, Ni, Cr, Al and Ti of 8:8:2:1:1;
[0062] S2. Place the above alloy raw materials in a water-cooled non-consumable vacuum arc melting furnace in the order of melting point from low to high and size from small to large, evacuate to below 0.005Pa, fill the furnace cavity with argon gas to flush, repeat three times, and then open the arc under the protection of argon gas. The initial arc current is 60-80A, and then gradually increased to 150A to melt the titanium ingot; then move to the raw materials to be smelted, gradually melt the raw materials along the water-cooled copper crucible, and then increase the current to 200A, stay for about 10s, so that the alloy is melted into button ingots; repeat the smelting process 4 times to make the alloy components fully melted and evenly diffused;
[0063] S3, using the copper mold suction casting method, the fully smelted alloy is kept at an arc of 180A for 10 to 20 seconds and then the melt is cast into a plate-shaped water-cooled copper mold (10 mm wide, 5 mm thick, and 60 mm high) to obtain a corresponding plate-shaped alloy product with a thickness of 5 mm;
[0064] S4, placing the alloy product in a heat treatment furnace at 1200° C. for homogenization for 2 h, and then water-cooling to room temperature;
[0065] S5, subjecting the homogenized alloy product to multiple cold rolling processes until the rolling reduction is 85%;
[0066] S6. The alloy product after cold rolling is subjected to aging annealing at 600° C. for 8 h and then water-cooled to room temperature to obtain the cobalt-free high entropy alloy.
[0067] Comparative Example 1
[0068] Compared with Example 1, the only difference is that the molar ratio of Fe, Ni, Cr, Al and Ti in step S1 is 1:1:1:1:1, and the prepared material is rolled as follows: Figure 2 As shown by Figure 2 It can be seen that rolling cracking occurred in Comparative Example 1 during the rolling process (red circle part).
[0069] Comparative Example 2
[0070] The alloys used in this comparative example are FeCrAl alloys, including C35MN, C35N, T35Y2 and APMT.
[0071] Test example
[0072] The tensile mechanics test was performed on the samples prepared in Example 1:
[0073] The tensile test was completed on an MTS-CMT5205 universal mechanical testing machine. The gauge length of the tensile specimen was 12.7 mm, the gauge length of the extensometer was 10 mm, and the strain rate was 0.001 s. -1 , tensile test results are as follows Figure 3 shown.
[0074] Figure 3 The tensile curves of the cobalt-free high entropy alloy prepared in Example 1 of the present invention at room temperature (a) and at 600°C (b), and the comparison with the room temperature tensile test results of the FeCrAl alloy (c).
[0075] Among them, Figure 3(a) It can be seen that the room temperature yield strength of the cobalt-free high entropy alloy prepared in Example 1 of the present invention in the cast state is about 500 MPa, the tensile strength is 922 MPa, and the tensile strain is 37%; the yield strength in the aged state is about 1.6 GPa, the tensile strength is about 1.7 GPa, and the tensile strain is 15%.
[0076] Depend on Figure 3 (b) It can be seen that the tensile strength of the cobalt-free high entropy alloy prepared in Example 1 of the present invention is about 700 MPa at 600°C.
[0077] Depend on Figure 3 (c) It can be seen that compared with FeCrAl alloys, the mechanical properties of Example 1 are better than those of FeCrAl alloys.
[0078] The crystal structure of the cobalt-free high entropy alloy prepared in Example 2 was characterized:
[0079] The crystal structure of the alloy was characterized by X-ray diffraction, with a scanning angle of 20-100° and a scanning speed of 4° / min. Figure 4 shown.
[0080] Figure 4 This is the X-ray diffraction pattern of the cobalt-free high entropy alloy prepared in Example 1. Figure 4 It can be seen that the cobalt-free high entropy alloy presents a single FCC structural phase (represented by the diamond in the figure).
[0081] The microstructure of the cobalt-free high entropy alloy prepared in Example 1 was characterized:
[0082] The microstructure of the alloy was analyzed using a SEM produced by Zeiss. Figure 5 and Figure 6 shown.
[0083] Figure 5 The SEM image (a) and the grain size statistics (b) of the cobalt-free high entropy alloy prepared in Example 1 of the present invention are shown in FIG. Figure 5 (a) shows the dense distribution of nanosheets inside the grains and at the grain boundaries; Figure 5 (b) reflects the grain size of the Co-free high-entropy alloy, with an average grain size of about 2 μm.
[0084] Figure 6 The nanoscale SEM image of the cobalt-free high entropy alloy prepared in Example 1 of the present invention shows that the second phase in the alloy is mainly in the form of two-dimensional nanosheets or nanorods, with a size of about 200nm×20nm on a two-dimensional scale, and is densely distributed, with a high volume fraction in the alloy. Figure 3 From the tensile properties of the alloy in the intermediate-aged state, it can be judged that this structure makes a great contribution to the excellent mechanical properties of the alloy.
[0085] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0086] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A cobalt-free high entropy alloy, characterized in that: The alloy raw material consists of 38-42 parts of Fe, 40-44 parts of Ni, 8-12 parts of Cr, 1-4 parts of Al and 3-6 parts of Ti by mass; The preparation steps of the cobalt-free high entropy alloy include: performing vacuum arc melting on the alloy raw material under the protection of argon atmosphere to obtain an alloy product; performing homogenization treatment, cold rolling treatment, and annealing treatment on the alloy product to obtain the cobalt-free high entropy alloy; The vacuum arc melting step comprises: the initial arc current is 60-80A, gradually increasing to 145-155A to melt the alloy raw materials, and then increasing the current to 200A and maintaining it for 8-12 seconds to complete the melting; The vacuum arc melting is performed at least once, and the vacuum degree is not higher than 0.005 Pa; The temperature of the homogenization treatment is 1150-1250° C., and the time is 2-4 hours; the rolling reduction of the cold rolling treatment is 75-85%; the temperature of the annealing treatment is 600-750° C., and the time is 1-8 hours.
2. The cobalt-free high entropy alloy according to claim 1, characterized in that: The molar ratio of Fe, Ni, Cr, Al and Ti in the alloy raw material is 8:8:2:1:
1.
3. A method for preparing a cobalt-free high entropy alloy according to any one of claims 1 to 2, characterized in that the steps include: The alloy raw materials are subjected to vacuum arc melting under the protection of an argon atmosphere to obtain an alloy product; The alloy product is subjected to homogenization treatment, cold rolling treatment and annealing treatment to obtain the cobalt-free high entropy alloy.
4. The preparation method according to claim 3, characterized in that: The vacuum arc melting step includes: the initial arc current is 60-80A, gradually increasing to 145-155A to melt the alloy raw materials, and then increasing the current to 200A and maintaining it for 8-12s to complete the melting.
5. The preparation method according to claim 4, characterized in that: The vacuum arc melting is performed at least once, and the vacuum degree is not higher than 0.005Pa.
6. The preparation method according to claim 3, characterized in that: The temperature of the homogenization treatment is 1150-1250° C., and the time is 2-4 hours; the rolling reduction of the cold rolling treatment is 75-85%; the temperature of the annealing treatment is 600-750° C., and the time is 1-8 hours.
7. Use of the cobalt-free high entropy alloy as claimed in any one of claims 1 to 2 as a high-strength structural material in the nuclear industry.
Citation Information
Patent Citations
Low-cost, high-strength and high-toughness mid-entropy alloy and preparation method
CN111961946A